Proses Faset Manual dan Pemasangan Lensa Polycarbonate pada Frame Semi Rimless - Aprilia Dwi Praptama; Adi Cahyono; Sri Suharti (EMVIRO Jurnal Ilmiah Penelitian Kesehatan, 2024)
Polycarbonate is an organic lens developed since the 1970s, initially used by space crews as helmet glass. However, it was only in the 1980s that polycarbonate lenses entered the market as lenses for glasses. Known for being lightweight, thin, impact-resistant, and non-breakable, polycarbonate lenses are perfect for athletes and children who often engage in outdoor activities. Additionally, these lenses are highly suitable for rimless and semi-rimless frames due to their durability. One of the notable features of polycarbonate lenses is their thinner thickness compared to other lenses, which presents challenges for facet practitioners during the edging or cutting process. The creation of grooves for hidden bevels in semi-rimless frames requires extra caution to prevent damage to the edges of the lens. The research on facet activities is conducted using observational and descriptive methods, focusing on facet processing techniques. Specifically, facet processing done using a dry facet method not only saves time but also results in cleaner outcomes for polycarbonate lenses. This study emphasizes the importance of precision and careful handling in facet activities to ensure the durability and functionality of polycarbonate lenses in eyewear. By understanding these processes, practitioners can minimize errors and improve the overall quality of lens fitting.